Women’s Labors in International Market: Mother’s Love, Agency and Plurality of Activism Politics - Candraningrum, Dewi (Yayasan Jurnal Perempuan, 2015)
Activism of international women’s labors does not deal with one version of global action yet manifesting in pluralism of actions with divergent and different forms. Many faces of Asia-Pacifics women’s movements, for example, are having multiple expressions in engaging with emancipatory politics at all levels. Effort to generalize their fights, resistance, and resilience will at the end reduce the capacity of their political movement in terms of framework, tradition, generation, ethnicity and nationalism. Women are collectively challenging the injustice, violence, and inequality by demonstrating differences which are linguistically, geographically and culturally defined. Thus, flexibility of action and resilience is the best cure to patriarchy. Keywords: